Service Quality and Corporate Image through Customer Satisfaction and Their Impact on Customer Loyalty of Bank Syariah Indonesia - Zakiah, Nurul; Umiyati, Umiyati (Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study aims to examine and analyze the effects of service quality and corporate image variables on customer satisfaction and their impact on customer loyalty. This study uses primary data by distributing questionnaires to customer of Bank Syariah Indonesia (BSI) KCP Depok Sawangan Raya. The numbers of samples in this research is 100 respondents and uses a purposive sampling method. The method used in this study is Partial Least Square (PLS) using a data analysis tool, namely SmartPLS 3.0. The results of this study indicate that the quality of service has a significant effect on customer satisfaction, while corporate image does not have a significant effect on customer satisfaction. The quality of service has a significant effect on customer loyalty, while the corporate of image has no significant effect on customer loyalty. Service quality has a significant effect on customer loyalty through customer satisfaction, while corporate image has no significant effect on customer loyalty through customer satisfaction.